2017
DOI: 10.1111/ijn.12601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aromatherapy massage on anxiety, depression, and physiologic parameters in older patients with the acute coronary syndrome: A randomized clinical trial

Abstract: Aromatherapy massage can be considered by clinical nurses an efficient therapy for alleviating psychological and physiological responses among older women suffering from acute coronary syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 49 publications
0
26
1
2
Order By: Relevance
“…The intervention in these studies was inhalation aromatherapy 27,[36][37][38][39][40][41][42] or aromatherapy massage 35,40 with lavender. Aromatherapy with lavender essential oil was conducted on the patients suffering from migraine, 41 patients with the acute coronary syndrome, 35 patients undergoing hemodialysis, 27,39 community-dwelling older adults, 36,40 and postpartum depression. 37,38,40 Depression was measured by different scales, including Hospital Anxiety and Depression Scale (HADS), Geriatric Depression Scale (GDS), Beck Depression Inventory (BDI), Depression Anxiety Stress Scales-21, Center for Epidemiological Studies Depression (CES-D) Scale, and Edinburgh Anxiety Questionnaire and Stress Scale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention in these studies was inhalation aromatherapy 27,[36][37][38][39][40][41][42] or aromatherapy massage 35,40 with lavender. Aromatherapy with lavender essential oil was conducted on the patients suffering from migraine, 41 patients with the acute coronary syndrome, 35 patients undergoing hemodialysis, 27,39 community-dwelling older adults, 36,40 and postpartum depression. 37,38,40 Depression was measured by different scales, including Hospital Anxiety and Depression Scale (HADS), Geriatric Depression Scale (GDS), Beck Depression Inventory (BDI), Depression Anxiety Stress Scales-21, Center for Epidemiological Studies Depression (CES-D) Scale, and Edinburgh Anxiety Questionnaire and Stress Scale.…”
Section: Resultsmentioning
confidence: 99%
“…37,38,40 Depression was measured by different scales, including Hospital Anxiety and Depression Scale (HADS), Geriatric Depression Scale (GDS), Beck Depression Inventory (BDI), Depression Anxiety Stress Scales-21, Center for Epidemiological Studies Depression (CES-D) Scale, and Edinburgh Anxiety Questionnaire and Stress Scale. The results obtained from studies showed the positive effect of aromatherapy with lavender essential oil on depression, 27,[35][36][37][38][39][40] whereas some studies did not report the positive effect of aromatherapy with lavender on depression significantly. 41,42 Other details are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding DBP, only one trial [22] showed a significant anxiolytic effect, and the remaining trials showed no significant effect. The mean effect was À0.17 (95% CI, À0.37 to 0.04, p ¼ .11) and the treatment effects showed no inconsistency across the studies (t 2 ¼ 0.00, c 2 ¼ 4.22, df ¼ 5, p ¼ .52, I 2 ¼ 0%).…”
Section: Anxiolytic Effects Of Lavender Aromatherapy On Physiologic Mmentioning
confidence: 93%
“…Vital signs were measured in six trials [32,34,35,39], and each meta-analysis was performed according to SBP, DBP, and heart rate. Regarding SBP, only one trial [22] showed a significant anxiolytic effect, with an effect of À0.56 (95% CI, À0.98 to À0.14), while the remaining trials showed no significant anxiolytic effect. However, the SMD (Hedges'ĝ) was À0.22 [95% CI, À0.43 to À0.02), indicating that lavender aromatherapy significantly decreased participants' SBP.…”
Section: Anxiolytic Effects Of Lavender Aromatherapy On Physiologic Mmentioning
confidence: 96%